Fuzuloparib with or without apatinib as maintenance therapy in newly diagnosed, advanced ovarian cancer (FZOCUS‐1): A multicenter, randomized, double‐blind, placebo‐controlled phase 3 trial - Lingying Wu; Jing Wang; Qingshui Li; Danbo Wang; Cuiying Zhang; Junying Tang; Guonan Zhang; Min Hao; Desheng Yao; Qinglei Gao; Youzhong Zhang; Ruifang An; et al. (CA: A Cancer Journal for Clinicians, 2026)
Abstract Although poly(adenosine diphosphate‐ribose) polymerase inhibitors (PARPis) and bevacizumab were approved as first‐line maintenance for advanced ovarian cancer (OC), evidence comparing this combination with PARPi monotherapy, especially in BRCA ‐mutated/homologous recombination‐deficient (HRD) patients, is lacking. This study compared combined fuzuloparib (a PARPi) plus apatinib (a vascular endothelial growth factor receptor‐2 inhibitor) with either fuzuloparib or placebo as first‐line maintenance in patients with advanced OC. Patients who had newly diagnosed, advanced OC and responded to first‐line, platinum‐based chemotherapy were randomized 2:2:1 to receive combined fuzuloparib (100 mg twice daily) plus apatinib (375 mg daily), fuzuloparib (150 mg twice daily) plus placebo, or double‐placebo treatment. The primary end point was blinded independent review committee (BIRC)‐assessed progression‐free survival (PFS). Six hundred seventy‐four patients were randomized to receive fuzuloparib plus apatinib ( n = 269), fuzuloparib ( n = 269), or placebo ( n = 136). At the final analysis (November 1, 2024; 385 BIRC‐assessed PFS events; median follow‐up, 40 months), the median BIRC‐assessed PFS was 26.9 months with the combination versus placebo (hazard ratio [HR], 0.57; 95% confidence interval [CI], 0.44–0.75; one‐sided p < .0001) and 29.9 months with fuzuloparib monotherapy versus placebo (HR, 0.58; 95% CI, 0.44–0.75; one‐sided p < .0001) compared with 11.1 months with placebo. A PFS benefit was observed regardless of germline BRCA1/2 mutation status. In homologous recombination‐deficient patients (including those with BRCA1/2 mutations), combined fuzuloparib and apatinib produced a PFS similar to that of fuzuloparib (34.1 vs. 35.8 months, respectively); in homologous recombination‐proficient patients, PFS had a trend favoring the combination (16.6 vs. 11.0 months; HR, 0.73; 95% CI, 0.45–1.19). Both treatments were well tolerated. Overall survival was immature. Both fuzuloparib and combination therapy improved PFS compared with placebo as maintenance therapy for patients who had newly diagnosed, advanced OC. Adding apatinib to fuzuloparib did not prolong PFS among homologous recombination‐deficient patients. There was a PFS benefit trend among homologous recombination‐proficient patients who received combination therapy compared with those who received monotherapy.